Analisis Pengendalian Persediaan Bahan Baku dengan Menerapkan Metode Economic Order Quantity : Studi Kasus pada Pabrik Tahu Mr di Ciawi Kabupaten Tasikmalaya - Rekha Puspita; Arga Sutrisna; Kusuma Agdhi Rahwana (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine how to control the inventory of raw materials at the MR Tofu Factory. How is the application of the Economic Order Quantity (EOQ) method in controlling raw material inventory at the MR Tofu Factory, Is there a difference between controlling raw material inventory at the MR Tofu Factory without using the EOQ method and using the EOQ method. The main raw material used in the MR Tofu Factory is soybeans. The method used in this research is Mixed Methods. Data analysis using EOQ, Safety Stock, Reorder Point, and Total Inventory Cost methods. In this study calculate the method of Economic Order Quantity (EOQ). Companies can find out the total cost of raw material inventory so that the purchase of raw materials is economical and minimizes inventory costs. After that, the results of the paired sample t-test were carried out that there was a significant difference from the data results without using the EOQ method and using the EOQ method.